2013
DOI: 10.1016/j.neuroimage.2013.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sutures and fontanels on MEG and EEG source analysis in a realistic infant head model

Abstract: In infants, the fontanels and sutures as well as conductivity of the skull influence the volume currents accompanying primary currents generated by active neurons and thus the associated electroencephalography (EEG) and magnetoencephalography (MEG) signals. We used a finite element method (FEM) to construct a realistic model of the head of an infant based on MRI images. Using this model, we investigated the effects of the fontanels, sutures and skull conductivity on forward and inverse EEG and MEG source analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 71 publications
6
102
0
Order By: Relevance
“…Specifically, the influence of a human skull defect on the MEG signals should be strongest if the source is central beneath the defect. A neonatal simulation study supports this finding (Lew et al, 2013). In the following, we evaluate the differences between our experiment and potential human recordings.…”
Section: Interpretation For Human Meg and Eegsupporting
confidence: 53%
See 3 more Smart Citations
“…Specifically, the influence of a human skull defect on the MEG signals should be strongest if the source is central beneath the defect. A neonatal simulation study supports this finding (Lew et al, 2013). In the following, we evaluate the differences between our experiment and potential human recordings.…”
Section: Interpretation For Human Meg and Eegsupporting
confidence: 53%
“…The qualitative observations should be transferable to burr holes in humans. This is supported by a neonatal simulation study (Lew et al, 2013) that showed that the MEG and EEG signals of sources beneath neonate thin sutures are influenced by these sutures. Larger skull defects should cause a wider spread of signal changes.…”
Section: Interpretation For Human Meg and Eegmentioning
confidence: 67%
See 2 more Smart Citations
“…In EEG source problem, neural sources are reconstructed inside the brain based on electric potential measurements around the scalp, and it is well known that the inverse solution depends strongly on the accuracy of discretized head geometry [2,4,7,8,16,39,49,54] and the accuracy of electric conductivity modelling of different tissues [3,47,25,48,34,50,51]. The head features can be extracted, to some extent, by using multi-modal imaging (computed tomography / diffusion magnetic resonance imaging), for example.…”
Section: Introductionmentioning
confidence: 99%